2017
DOI: 10.3389/fped.2017.00180
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Perinatal Oxycodone Exposure on Behavioral Outcome in a Rodent Model

Abstract: Opiate addiction is now a major public health problem. Perinatal insults and exposure to opiates such as morphine in utero are well known to affect development of the hypothalamic–pituitary–adrenal axis of the offspring adversely and are associated with a higher risk of developing neurobehavioral problems. Oxycodone is now one of the most frequently abused pain killers during pregnancy; however, limited data are available regarding whether and how perinatal oxycodone exposure (POE) alters neurobehavioral outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 88 publications
(97 reference statements)
3
30
3
Order By: Relevance
“…Orally-administered analgesics are the most common form of pain relief prescribed after caesarian sections 12,13 , and oral oxy administration has been shown to be safer than and as effective as intravenous administration of other opioids 9,14,15 . Previous oxy studies have shown deficits such as behavioral impairments and disruption in both OPRM1 and endothelin receptor expression during development in offspring exposed to oxy in utero [16][17][18][19] . However, these studies focused primarily on prenatal oxy exposure, leaving a large gap in the knowledge regarding postnatal oxy exposure.…”
Section: Introductionmentioning
confidence: 95%
“…Orally-administered analgesics are the most common form of pain relief prescribed after caesarian sections 12,13 , and oral oxy administration has been shown to be safer than and as effective as intravenous administration of other opioids 9,14,15 . Previous oxy studies have shown deficits such as behavioral impairments and disruption in both OPRM1 and endothelin receptor expression during development in offspring exposed to oxy in utero [16][17][18][19] . However, these studies focused primarily on prenatal oxy exposure, leaving a large gap in the knowledge regarding postnatal oxy exposure.…”
Section: Introductionmentioning
confidence: 95%
“…However, a human study by Seaton et al has shown that oxy is concentrated in the breastmilk and offspring exposed via the breastmilk may receive less than 10% of a typical therapeutic oral infant dose (0.1-0.2 mg/kg) [32][33][34][35][36]. Despite this low dose, infant exposure to oxy via the breastmilk has been associated with central nervous system depression [37], and a number of animal studies have also revealed deficits in behavior and development associated with perinatal opioid exposure [12,[38][39][40]. Additionally, opiates can pass into the placenta and act on fetal opioid receptors [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal opioid exposure has also been shown to induce hyperactivity upon novelty in adolescent and adult offspring (Lasky et al, 1977;Zhu and Stadlin, 2000;Timár et al, 2010;Sithisarn et al, 2017). Interestingly, a link between an animal's hyperactivity in a novel environment and a higher propensity for developing drug sensitization or drug selfadministration has been proposed for several classes of drugs, including opioids (Piazza et al, 1989;Piazza and Le Moal, 1996;Suto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%